Dai De's records of ritual: the "Da Dai Liji" - Hsu, Nai-Yi; Ing, Michael David Kaulana (Studies in the history of religions, 2025)
"Dai De's Records of Ritual is a collection of 40 texts purporting to record the teachings of ancient Chinese rulers as well as the teachings of Confucius, his disciples, and his later followers on topics, broadly speaking, about creating society and ordering the world. The original collection contained over 80 texts, first collected sometime around the first century BCE, with Dai De as the attributed editor. By the sixth century CE, a number of texts were lost, leaving the Da Dai Liji in its received form, which is presented here in English alongside the Chinese"-- Provided by publisher